The challenges experienced by teenage mothers in secondary schools : the case of Hlanganani South Circuit - Chauke, Helen (University of Limpopo (Turfloop Campus), 2013)
This qualitative study was conducted to explore the challenges experienced by teenage mothers in Hlanganani South Circuit Secondary Schools in the Vhembe District in Limpopo, South Africa. Hlanganani South circuit is made up of seven secondary schools and out of these seven three were sampled because of their vicinity and the high number of teenage mothers in them. A purposive sample was conducted wherein twelve teenage mothers aged between twelve to eighteen years, three educators and three School Management Team members from these secondary schools were sampled to explore the challenges that teenage mothers come across in these schools. Data were collected using two methods, namely: semi structured interview and documents analysis. Semi structured interviews were used to gather information from both teenage mothers and educators while documents such as period registers, attendance registers, morning study registers, permission register, winter enrichment programme registers, afternoon study register, quarterly schedules and continuous assessment tasks were used to explore the challenges faced by teenage mothers in secondary schools. Data from semi structured interview with teenage mothers were analysed and the following themes and categories emerged: difficulty in balancing schooling and motherhood, negative attitude by educators towards teenage mothers, negative attitude of peers, lack of extra lessons/catch up programmes for teenage mothers, lack of optional tasks/tests for teenage mothers, lack of counselling and support for teenage mothers, and lack of structures for teenage mothers. On analysing data from educators, the following categories emerged: lack of cooperation from teenage mothers, lack of commitment by teenage mothers on academic matters, poor school attendance, lack of time for extra lessons, and lack of time for optional tasks/tests. The analysis of data from documents indicated habitual absenteeism, dodging of lessons (morning and afternoon), missing tasks and poor performance by teenage mothers. The key findings of the transcribed interviews indicated that teenage mothers had difficulty in balancing schooling and taking care of their children, because they lacked support from their educators, peers, parents and the community at large. In order for teenage mothers to succeed with their schooling, maximum support is needed from all stake holders, that is peers, parents, educators and the whole community structures.
Thesis (M.Ed. (Curriculum Studies) --University of Limpopo, 2013
Keywords: Teenage mothers; School management; 306.874368257; Teenage mothers; Young mothers